Beda Persepsi Dokter Puskesmas Integrasi dan Non Integrasi di Kabupaten Klaten terhadap Penderita Skizofrenia - Anisa Renang, Carla Marchira (Berita Kedokteran Masyarakat (BKM), 2009)
Background: Mental disorder  is a health problem commonly  found in  the community. Studies showed that mental disorder  often  undetected  and  not well managed  in  primary  care.  Primary  care  doctors  perception  towards severe mental disorder  i.e. schizophrenia will  influence  the management  of  this  disorder.Objective: To  identify  different  perception  between  integration  and  non-integration  primary  care  doctor  in Klaten  regency  towards  schizophrenia  patient.Subject  and Method: Subjects were  primary  care  doctors  in Klaten Regency. The  figure of  sample was  48. Data was  collected  using  perception  towards schizophrenia  patient  instrument. Data was  analyzed with Chi-Square.Result: Data  collection  showed  75%  primary  care  doctors  stated  that  schizophrenia was  a  disease which could be  recovered, 45.8% stated  they did not  like  to  treat schizophrenia patient, 83.3% stated  that schizophrenia patient  needed  to be  supervised continuously,  and 16.7%  primary care  doctors stated  that schizophrenia  patient is  dangerous;  therefore  they  needed  to  be  isolated. Chi-square  test  showed  different  perception  between integration  and  non-integration  primary  care  doctor  towards  recovery  of  schizophrenia  patient    (x²=7.759, p=0.005),  using of  new  antipsychotic  (x²=9,966, p=0,002),  supervision  of  schizophrenia  patient  continuously (x²=12.448,  p=0.00),  giving  diagnosis  of  schizophrenia  (x²=5.828,  p=0.016)  and  isolation  of  schizophrenia patient    (x²=12.448,  p=0.00).Conclusion:  There’s  a  significant  difference  between  integration  and  non-integration  primary  care  doctor towards  recovery  of  schizophrenia  patient,  using  of  new  antipsychotic,  supervision  of  schizophrenia  patient continuously,  giving diagnosis  of schizophrenia,  and  isolation  of  schizophrenia  patient.Keywords:  perception, primary  care doctor,  schizophrenia